Repurposing end of life notebook computers from consumer WEEE as thin client computers – A hybrid end of life strategy for the Circular Economy in electronics. (10th August 2018) - Coughlan, Damian; Fitzpatrick, Colin; McMahon, Muireann
Abstract: This paper presents an investigation into the feasibility of repurposing end-of-life notebook computers as thin client computers. Repurposing is the identification of a new use for a product that can no longer be used in its original form and has the potential to become a hybrid re-use/recycling end-of-life strategy for suitable e-waste when direct reuse is not economically or technically feasible. In this instance, it was targeted to produce thin client computers using motherboards, processors and memory from used laptops while recycling all other components. Notebook computers are of interest for this type of strategy due to having a substantial environmental impact in manufacturing but often not having the option of direct reuse as they are prone to damage and experience a rapid loss of value over time. They also contain multiple critical raw materials with very low recycling rates. The notebook computers were sourced from Civic Amenity sites (CA) and originated from business-to-consumer (B2C) channels. A total of 246 notebook computers were collected and analysed. The paper outlines a methodology developed to identify, test, analyse, and disassemble suitable devices for repurposing. The methodology consists of the following stages with associated pass rates; Visual Inspection & Power-on Test (32%) the Initial-stage functionality test comprised of Functionality Test (56%), Diagnostics (100%) and Benchmarking (86%). The Disassembly stage had a pass rate of 100% and the Post-Disassembly Test comprised of a Validation test (86%). The Final-stage functionality test had a pass rate of 61%. The overall results show that 9% of the notebook computers were suitable for repurposing as thin client computers. It recommends the following design changes to notebooks/laptops that would support repurposing; 1) PCB mounted Fan and Heatsink assembly, 2) Eliminate daughter and I/O boards, 3) A separate Power Button assembly, 4) Reduction in size of the motherboards surface area or physical size. These design changes would allow for a more efficient transition for a change of role. A streamlined lifecycle analysis based on Cumulative Energy Demand (CED) was undertaken to compare the impact of repurposed notebook computers with new thin client computers. The results indicated that there are significant potential savings to be made by extending lifetimes and offsetting the production of new thin client computers under a range of assumptions. Highlights: The Repurposing of notebook computers to thin clients has been demonstrated. Repurposing is suitable for notebooks that are not feasible for direct reuse. Design criteria for repurposing EoL notebooks as thin clients have been identified. A Streamlined Lifecycle Analysis confirms the environmental benefits.